Does previous cesarean section influence neonatal birth weight? A path analysis in China. Issue 1 (February 2019) - Qin, Chunxiang; Deng, Yulong; Chen, Wei-ti; Mi, Chunmei; Wang, Weiyan; Sun, Mei; Chen, Jiarui; Liu, Wei; Tang, Siyuan
Abstract: Background: Since the One-child Policy was revised to a Two-child policy in 2013, the number of pregnancies with previous cesarean section suddenly increased in China. The aim of this study was to test if a previous cesarean section influenced the neonatal birth weight under Chinese background. Methods: A retrospective study was conducted. Path analysis was used to test the hypothesized model for the association among previous cesarean section, placenta previa, gestational age and neonatal birth weight. Comparative fit index, the root-mean-square error of approximation and weighted root-mean-square residual were used to evaluate the model fit. Results: 3466 electronic records for second pregnancies met the criteria; a modified model was established (the root-mean-square error of approximation = 0.049, comparative fit index = 0.992, weighted root-mean-square residual = 0.960). The effects of previous cesarean section on neonatal birth weight were mediated via four paths. The direct effects (coefficient: 0.056) showed opposite signs compared to indirect effects (coefficient: −0.127) in this path analysis. It meant that the negative effects of the previous cesarean section were suppressed by other factors which bring positive effects. Conclusion: This study showed that previous cesarean section had negative effects on neonatal birth weight with increasing incidence of placenta previa and preterm birth. But these effects were suppressed by other positive factors, such as maternal body mass index, just after the child policy updated in China.